The Contrast Between Demographic Variables and Internet Use: A Study of University Students - Rojas-Kramer, Carlos A; Santana, Josefina C; Escalera-Chávez, Milka E (TEM Journal, 2022)
The objective of this research is to test whether the use of the Internet becomes problematic in the lives of university students and how demographic variables impact the subject of study. The InternetRelated Experiences (CERI) questionnaire proposed by Beranuy et al. (2009) was used. The results reveal that 77% of students have problems using the Internet, and 40% have frequent issues using the Internet. Additionally, the results show evidence that there is no difference in the level of internet use between the gender and age variables, however, with reference to the semester they are studying, there is a significant difference.